Tissue-specific knockout of E-cadherin (Cdh1) in developing mouse gonads causes germ cells loss. Issue 2 (August 2019) - Piprek, Rafal P; Kolasa, Michal; Podkowa, Dagmara; Kloc, Malgorzata; Kubiak, Jacek Z
Abstract : The normal course of gonad development is critical for the sexual development and reproductive capacity of the individual. During development, an incipient bipotential gonad which consists of unorganized aggregate of cells, must differentiate into highly structured testis or ovary. Cell adhesion molecules (CAMs) are a group of proteins crucial for segregation and aggregation of different cell types to form different tissues. E-cadherin ( Cdh1 ) is one of the CAMs expressed in the developing gonads. We used tissue-specific knockout of Cdh1 gene in OCT4 + germ cells and, separately, in SF1 + somatic cells of developing gonads. The knockout of E-cadherin in somatic cells caused decrease in the number of germ cells, while the knockout in the germ cells caused their almost complete loss. Thus, the presence of E-cadherin in both the germ and somatic cells is necessary for the survival of germ cells. Although the lack of E-cadherin did not impair cell proliferation, it enhanced apoptosis, which was a possible cause of germ cell loss. However, the somatic cells of the gonad differentiated normally into Sertoli cells in the testis cords, and into follicular cells in the ovaries. The testis and ovigerous cords maintained their integrity; they were covered by continuous basement membranes. The testicular interstitium with steroidogenic fetal Leydig cells did not show any noticeable changes. However, in the female gonads, because of the lack of germ cells, the ovarian follicles were absent. The sex determination and sexual differentiation of the gonad were not impaired. These results underscore an important role of E-cadherin in germ cell survival and gonad development.